Keindahan Terselubung Web Series Sore : Kajian Estetika - Destyanisa Tazkiyah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This article discusses the aesthetic assessment of the web series Sore which is done through a semiotic approach, as well as the beauty of delivering the moral message behind the purpose of the web series as advertisement. The first step on the research is to develop basic narrative scheme to guide the determination of the main signifiers in the web series. Next is to analyze the style of language contained in the dialogue that has a metaphor in it. And finally, the aesthetic assessment of the delivery of moral messages in the web series. After analyzing the authors found the hidden beauty of the web series Sore is the simple form of main signifier, the use of metaphors that have beauty as supporting the delivery of the meaning in some scenes on the web series, as well as the web series successfully deliver the moral messages with such a natural and beautiful scene that accordance with the purpose of literature to entertain and educate.